Catalytic reforming of palm kernel shell microwave pyrolysis vapors over iron-loaded activated carbon: Enhanced production of phenol and hydrogen. (June 2020) - An, Yang; Tahmasebi, Arash; Zhao, Xiaohui; Matamba, Tawanda; Yu, Jianglong
Highlights: Fe/AC catalyst proved effective in reforming PKS pyrolysis vapors under microwave. Fe/AC catalyst greatly promoted the selectivity of H2 and phenol formation. The concentration of phenol in bio-oil reached 75.09 area% via catalytic reforming. The concentration of H2 reached a maximum of 75.12 vol% over 2%-Fe/AC catalyst. The Fe/AC catalyst promoted the demethoxylation and deoxygenation reactions. Abstract: This study addresses the in-situ microwave catalytic reforming of volatile matter from palm kernel shell (PKS) over iron-loaded activated carbon (Fe/AC) catalysts. The impacts of catalyst composition on the secondary gas-phase reactions and distribution of products were studied at 500 °C. It was found that the Fe/AC catalyst promoted the yield of light gases. Using the 1%-Fe/AC catalyst, the yield of gaseous fraction peaked at 37.09 wt%. The selectivity of the deoxygenated products was promoted in the presence of Fe. Catalytic reforming of PKS pyrolysis vapors over Fe/AC drastically enhanced the generation of phenol and H2, the concentrations of which reached 75.09 area% and 75.12 vol%, respectively. Catalytic pyrolysis of syringol and guaiacol as model compounds showed that Fe/AC catalyst promoted the demethoxylation and deoxygenation reactions to selectively generate phenol which was explained by oxophilic reactivity of the active Fe sites.